May her likes be multiplied : biography and gender politics in Egypt - Booth, Marilyn (University of California Press, 2001)
This study explores the Arabic tradition of life-writing in Egypt. It examines biographical works by women and uses examples of "famous women" biographies - including Joan of Arc and Jane Austen - to demonstrate how these narratives prescribed complex role models for middle-class girls
Keywords: Women -- Biography -- History and criticism.; Biography as a literary form.; Women -- Political activity -- Egypt -- History.; Feminism -- Egypt -- History.; Biography.; Femmes -- Biographies -- Histoire et critique.; Biographie (Genre littéraire); Femmes -- Activité politique -- Égypte -- Histoire.; Féminisme -- Égypte -- Histoire.; Biographies.; biographies (literary genre); biography (general genre); BIOGRAPHY & AUTOBIOGRAPHY -- Women.; Biography as a literary form; Feminism; Women -- Biography; Women -- Political activity; Egypt; Biografische Literatur; Frauenliteratur; Ägypten; Geschichte 1879-1967.; Criticism, interpretation, etc.; History